City of Tampa Urban Ecological Analysis - Michael G. Andreu; Melissa H. Friedman; Shawn M. Landry; Robert J. Northrop (EDIS)
FOR-203, a 2-page executive summary by Michael G. Andreu, Melissa H. Friedman, Shawn M. Landry, and Robert J. Northrop, summarizes a report of an ecological assessment of the city of Tampa’s urban forest resources. Published by the UF School of Forest Resources and Conservation, December 2008.